Comparing French carpoolers and non-carpoolers: Which factors contribute the most to carpooling?. (January 2016) - Delhomme, Patricia; Gheorghiu, Alexandra
Highlights: The aim was to identify the reasons for using or not carpooling. Carpoolers and non-carpoolers were similar in terms of yearly mileage, distance to their workplace/school, and public transportation accessibility. Carpoolers were more concerned about environmental threats than were non-carpoolers. These results suggest various strategies for increasing carpooling. Abstract: Carpooling is an effective solution to major environmental problems but it is insufficiently used, particularly in France. In order to increase carpooling, it is important to understand why people do or not carpool. This study, carried out a large sample of drivers, was aimed at (1) identifying whether or not people carpool, (2) investigating the factual data (e.g. socio-demographics, transportation accessibility) and motivational factors (e.g. attitudes regarding car use, public transportation, environment) upon which carpoolers and non-carpoolers differ, and (3) highlighting the main determinants of the practice of carpooling. An online survey was administered to 1207 French drivers (48% men, ages 19–87) recruited by means of a random-quota method. In our sample, 52.5% of the participants said they were using carpooling. Carpoolers and non-carpoolers were similar in terms of kilometers driven per year, distance to their workplace or schools/universities, and public transportation accessibility. Compared to non-carpoolers, carpoolers were more likely to be women, have children, have positive attitudes toward public transport, and be more environmentally aware. These results suggest various different strategies for increasing the number of carpoolers and the frequency of carpooling use by taking into account the gender of road users.